Cost Analysis of Inpatient Stroke Treatment at PKU Muhammadiyah Yogyakarta Hospital Based on INA-CBG's Tariff in 2023 - Hadning, Ingenida; Oktaviani, Aulia (Borneo Journal of Pharmacy, 2025)
Stroke incidence in Yogyakarta Province is among the highest in Indonesia, frequently necessitating prolonged patient care and rehabilitation. The recent adjustment of INA-CBG's tariffs, as stipulated in Regulation of the Minister of Health of the Republic of Indonesia Number 3 of 2023, has increased reimbursement rates for inpatient hemorrhagic stroke (Classes 1, 2, and 3) and ischemic stroke (Class 1). Despite these revisions, many hospitals report disparities between operational costs and the INA-CBG's reimbursement rates. This study represents the first dedicated evaluation of INA-CBG's tariffs, specifically concerning the 2023 ministerial regulation, for inpatient stroke management. We aimed to ascertain the financial discrepancies between the average actual costs of inpatient stroke treatment and the updated INA-CBG's tariffs at PKU Muhammadiyah Yogyakarta Hospital. Employing an observational design with a cross-sectional approach, we retrospectively collected data from inpatient stroke patients treated between January and September 2023. Data analysis involved descriptive statistics and a one-sample t-test. The findings reveal that, for most cases, the average actual costs incurred by the hospital were significantly lower than the corresponding INA-CBG's tariffs, indicating a consistent profit margin for the institution.